Review and new species of Tiferonia Darlington, 1962 (Carabidae, Abacetini) - Will, Kipling W. (Zookeys, 2020)
Abstract. Darlington described Tiferonia based on T. parva from New Guinea. In this review, Tiferonia leytensissp. nov. is described from Leyte Island, Philippines, Tiferonia schoutedeni (Straneo, 1943) comb. nov. is transferred from Melanchrous Andrewes, and inclusion of Tiferonia brunnea (Jedlička, 1935) in the genus is confirmed. Characteristics of Tiferonia and genera that have been proposed as closely related to Tiferonia are discussed and a unique character, the post-ocular sulcus, shared among species of Tiferonia and Holconotus is proposed as a synapomorphy for these two genera. A key to identify adults of the four species of Tiferonia is provided.